Condensation heat transfer on patterned surfaces - Chatterjee, Abhra; Derby, Melanie M.; Peles, Yoav; Jensen, Michael K. (My University, 2013)
An experimental study of condensation heat transfer was carried out on a 25.4mm diameter surface using steam as the condensing fluid. Three surface conditions were studied: hydrophilic, hydrophobic, and a surface with patterns of distinct hydrophilic and hydrophobic regions. The effects of inlet vapor velocity, mass flux, and hydraulic diameter on the heat transfer coefficients were investigated. The inlet vapor velocity was varied from about 0.05m/s to about 5m/s and the hydraulic diameter was varied from 4.5mm to 32.5mm. Depending on the surface condition, the heat transfer coefficients showed different responses to the varying parameters of the experiments. For the hydrophilic surface, the heat transfer coefficient was observed to be up to 2.5 times lower than that for the hydrophobic surface with all other parameters unaltered. On the other hand, the surfacewith a pattern of distinct hydrophobic and hydrophilic regions showed heat transfer coefficients that were higher than that of the hydrophilic surface and lower than that of the hydrophobic surface. In both the patterned and the hydrophobic surfaces, the heat transfer coefficient was observed to increase significantly with mass flux, while for the hydrophilic surface, the heat transfer coefficient was observed to be affected much less by the mass flux. In all cases, the heat transfer coefficients increased with increasing heat flux and decreased with increasing wall sub-cooling. The effect of average quality of the steam showed little effect on the heat transfer coefficients.
Citation: Chatterjee, A., Derby, M. M., Peles, Y., & Jensen, M. K. (2013). Condensation heat transfer on patterned surfaces. International Journal of Heat and Mass Transfer, 66, 889–897. https://doi.org/10.1016/j.ijheatmasstransfer.2013.07.077
Keywords: Condensation; Vapor Space; Pattern; Hydrophilic